2012
DOI: 10.1021/pr201122w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Rifampicin Resistance Mechanisms in Brucella abortus Using MS-Driven Comparative Proteomics

Abstract: Mutations in the rpoB gene have already been shown to contribute to rifampicin resistance in many bacterial strains including Brucella species. Resistance against this antibiotic easily occurs and resistant strains have already been detected in human samples. We here present the first research project that combines proteomic, genomic, and microbiological analysis to investigate rifampicin resistance in an in vitro developed rifampicin resistant strain of Brucella abortus 2308. In silico analysis of the rpoB ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 66 publications
1
25
1
Order By: Relevance
“…In this study, we utilized a proteomics approach to identify Brucella-specific proteins and pathways affected by changes in global c-di-GMP levels. This approach detected over half the orfeome (ϳ1,900 proteins) of Brucella, significantly more than previously reported (typically Ͻ500 proteins) (38)(39)(40). In the attenuated, high-c-di-GMP-expressing ⌬bpdA mutant, proteins involved in cell wall biogenesis were upregulated compared to both 16M and the ⌬cgsB mutant.…”
Section: Discussionmentioning
confidence: 70%
“…In this study, we utilized a proteomics approach to identify Brucella-specific proteins and pathways affected by changes in global c-di-GMP levels. This approach detected over half the orfeome (ϳ1,900 proteins) of Brucella, significantly more than previously reported (typically Ͻ500 proteins) (38)(39)(40). In the attenuated, high-c-di-GMP-expressing ⌬bpdA mutant, proteins involved in cell wall biogenesis were upregulated compared to both 16M and the ⌬cgsB mutant.…”
Section: Discussionmentioning
confidence: 70%
“…Notably in these adaptive strategies, a small number of mutations ultimately result in complex and significant global changes in gene expression and protein synthesis. For instance, rpoB mutations foster the up-regulation of proteins involved in central metabolism (including nucleoside and nucleotide, amino acid, carbohydrate, lipid, and phospholipid biosynthesis), detoxification, signal transduction, protein synthesis, and cell envelope processes, to name a few, whereas cell division proteins are generally down-regulated (6,7). Streptomycin resistance, via rpsL mutation (encoding for ribosomal protein S12, a subunit of the 30S ribosome), leads to increased translational accuracy, slower overall translation, and has demonstrated late growth phase protein synthesis increases in comparison with the wild type (8).…”
mentioning
confidence: 99%
“…The proteomic profile of rifampicin-resistant Brucella abortus was examined and compared to that of a non-resistant strain using MS-drive comparative proteomics; the resistant strain contained a mutation in the rpoB gene. In the same study, 12 836 MS/MS spectra identified 6,753 peptides corresponding to 456 proteins, of which 39 were differentially regulated in the resistant strain and were involved in various metabolic pathways (Sandalakis et al 2012). From this study, it can be hypothesized that various proteins, such as pyruvate decarboxylase, urocanatehydratase, bifunctional protein FolD, and an aminotransferase class-III: maltose-binding protein could potentially regulate antibiotic resistance (Sandalakis et al 2012).…”
Section: Proteomicsmentioning
confidence: 78%
“…In the same study, 12 836 MS/MS spectra identified 6,753 peptides corresponding to 456 proteins, of which 39 were differentially regulated in the resistant strain and were involved in various metabolic pathways (Sandalakis et al 2012). From this study, it can be hypothesized that various proteins, such as pyruvate decarboxylase, urocanatehydratase, bifunctional protein FolD, and an aminotransferase class-III: maltose-binding protein could potentially regulate antibiotic resistance (Sandalakis et al 2012). Using an MS/MS technique, Piras et al (2012) were able to identify the proteins that were differentially regulated in a multidrug-resistant E. coli as those involved in the metabolic pathways, including malate dehydrogenase, fructose-bisphosphatealdolase, triosephosphateisomerase, phosphoglucomutase, and others.…”
Section: Proteomicsmentioning
confidence: 87%